2010
DOI: 10.1074/jbc.m109.041285
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystallographic Analysis of the 6-Aminohexanoate Cyclic Dimer Hydrolase

Abstract: We performed x-ray crystallographic analyses of the 6-aminohexanoate cyclic dimer (Acd) hydrolase (NylA) from Arthrobacter sp., an enzyme responsible for the degradation of the nylon-6 industry byproduct. The fold adopted by the 472-amino acid polypeptide generated a compact mixed ␣/␤ fold, typically found in the amidase signature superfamily; this fold was especially similar to the fold of glutamyl-tRNA Gln amidotransferase subunit A (z score, 49.4) and malonamidase E2 (z score, 44.8). Irrespective of the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…bonds between the residues and substrate. The oxyanion hole of amidases plays a crucial role in catalysis by stabilizing the tetrahedral intermediate (TI) or the transition state (TS) for formation and hydrolysis of the acyl-enzyme intermediate (17)(18)(19)25). It was found in our study that mutation of Gly175 to Ala175 resulted in a 3.2-fold increase in the activity of Pa-Ami, while mutation of Gly175 to any other amino acids or mutation of other amino acid residues located near the oxyanion hole abolished or led to extremely low activities toward 2-chloronicotinamide (data not shown).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…bonds between the residues and substrate. The oxyanion hole of amidases plays a crucial role in catalysis by stabilizing the tetrahedral intermediate (TI) or the transition state (TS) for formation and hydrolysis of the acyl-enzyme intermediate (17)(18)(19)25). It was found in our study that mutation of Gly175 to Ala175 resulted in a 3.2-fold increase in the activity of Pa-Ami, while mutation of Gly175 to any other amino acids or mutation of other amino acid residues located near the oxyanion hole abolished or led to extremely low activities toward 2-chloronicotinamide (data not shown).…”
Section: Figmentioning
confidence: 99%
“…To further elucidate the mechanism of the improved catalytic activity of the double mutant toward 2-chloronicotinamide, the substrate access tunnels of the wild type and the G175A/A305T mutant ( Fig. 3; Table 5) were also built and analyzed using the software program PyMOL with plugin CAVER3.0 (23)(24)(25). The tunnel analysis indicated that the bottleneck radius and length of the catalytic tunnel in the G175A/A305T mutant were 1.44 Å and 11.64 Å, respectively, compared with 1.13 Å and 11.99 Å in the wild type.…”
mentioning
confidence: 99%
“…Negoro's group also explained the catalytic mechanisms and evolution of enzymes from the ancestor enzymes NylB and NylA, based on X-ray analysis of crystallized enzymes. 89,90) "-Caprolactam is a starting material for nylon-6 manufacturing, and is assimilated by a P. aeruginosa strain. 91) A thermophilic bacterium, Geobacillus thermocatenulatus, has been suggested as a possible degrader of nylon-12 and 66 but not nylon-6, 92) but its enzymes have yet to be characterized.…”
Section: Polyacrylate 54)mentioning
confidence: 99%
“…We have studied the degradation of polymeric nylon-6 and the byproducts of the manufacture of nylon-6, namely 6-aminohexanoate oligomers (nylon oligomers), as a model system (Okada et al, 1983;Negoro, 2000). We found that three enzymes, 6-aminohexanoatecyclic dimer hydrolase (NylA; Yasuhira et al, 2010), 6-aminohexanoate-dimer hydrolase (NylB; Negoro et al, 2005;Ohki et al, 2006Ohki et al, , 2009Kawashima et al, 2009) and nylon hydrolase (NylC), are responsible for the degradation of nylon-6 and its related compounds.…”
Section: Introductionmentioning
confidence: 99%